SPATIAL MOBILITY AND LOCATION CHOICES OF HIGHLY SKILLED WORKERS - Ernest Miguelez; Rosina Moreno (European Regional Science Association (ERSA), 2011)
The aim of the present paper is to shed light on the determinants of geographical mobility and location choices of skilled individuals across the European regions. The most talented workers, e.g. inventors, move for a number of reasons, contributing in this manner to the geographical diffusion of knowledge as well as to reshape the geography of talent. Thus, geographic areas constitute nodes through which talent circulate, bringing knowledge from one place to another. By means of a gravity model, we will test whether social proximity between inventors' communities and the so-called National System of Innovation drive in- and out-flows of inventors between pairs of regions, above and beyond physical separation, as well as other pulling factors (amenities, economic conditions, and the like). As for the econometrics is concerned, in order to accommodate our estimations to the count nature of our dependent variable and the high number of zeros in it, zero inflated negative binomial models are used. Our first results point out to the importance of, still, geographical proximity in driving this phenomenon. However, social relationships, as well as institutional, or technological and cultural proximities, are also playing a preponderant role in mediating the mobility patterns of inventors across the European geography.
Keywords: 330